Grouper cage -culture device - YANG QINGSHAN; LIN GUOFU; YANG LIHUA; LIN GUOCONG; YANG WENGUANG (2016)
The utility model discloses a grouper cage -culture device, including rectangular shelf, the bottom of shelf is provided with breeds the net, be provided with a plurality of keg float of floating around the shelf, be provided with showy foam in the middle of the shelf, be provided with the support frame on the showy foam, be provided with the foodstuff storage box on the support frame, be connected with in the foodstuff storage box and feed the esophagus, it extends to outside the showy foam to feed the esophagus, be provided with the solenoid valve on hello the esophagus, the solenoid valve is connected with control module, control module is connected with the timer. The beneficial effects are that: reliable and stable, can regularly feed for the grouper and eat, reduce the cost of labor, labour saving and time saving.